Covid: Keeping you updated 18. Issue 8 (August 2020) - Harvey, Bill
Abstract : In a week where the dissemination of facts rather than the facts themselves have again dominated headlines, Bill Harvey focuses on a newly confirmed sign of illness and predictions about future disease rates and pattern